Downgrading employment of university graduates in Korea and policy implications. (2018) - Cho, Sungeun; Lee, Young-Min
This paper examined downgrading employment issues based on existing studies and discussed the causes and solutions regarding the downgrading employment of university graduates. Specifically, this paper will focus on the occurrence of downgrading employment in Korean society. The downgrading employment induced by causes and influential factors have brought about lower utilisation of human resources, reduced productivity, weakening stable labour market, crowding-out effects of labour market due to downgrading employment, and so on. To resolve these problems, efforts should be made to resolve the problem of downgrading employment respectively on each hierarchy encompassing the level of the nation, university and companies, and individuals.